Conditions that contributing the utilization and implementation of educational innovations at higher education: a review of the literature - Mirzajani, Hassan; Nawawi, Mokhtar; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini (2014)
Nowadays, use of ICT in higher education is one of the main consideration in educational improvements. Integrating ICT into the training procedures is extensively apparent as a critical assert in educational reforms. In spite of remarkable improvement higher education in many countries, integration of ICT into universities to be astonishingly low. The purpose of current paper is based on a review of 68 refereed article and dissertation that focused on introducing Ely's (1990) eight conditions that simplify implementation of an invention. Also identify which conditions more affected on successful implementation an innovation in higher education. The results shown that although there were important efforts and positive approaches toward the use of ICT in higher education, but the procedure of ICT integration at the university challenged factors that have effect on utilization of ICT by faculty members in universities. The review finding revealed that effective implementation of an innovation in higher education was dependent on the four significant factors included availability of resources, existence of knowledge and skills, availability of time, and leadership.